Searching for supersymmetry and its avatars. (11th November 2019) - Ellis, John
Abstract : Why continue looking for supersymmetry? Over and above the aesthetic and theoretical motivations from string theory, there are several longstanding pheno- menological motivations for TeV-scale super- symmetry, such as the electroweak scale, and the lightest supersymmetric particle as cold dark matter. Run 1 of the Large Hadron Collider (LHC) has actually provided three extra motivations, namely the stabilization of the electroweak vacuum, and successful predictions for the Higgs mass and couplings. How to look for it? There are several examples of emergent supersymmetry, the most recent being on the surfaces of topological insulators, and some sort of effective supersymmetry could be useful for boosting the power of laser arrays. At the LHC, attention is moving towards signatures that had previously been neglected, such as long-lived charged particles—which might be an opportunity for the MoEDAL experiment. This article is part of a discussion meeting issue 'Topological avatars of new physics'.